Diversity among principal and GABAergic neurons of the anterior olfactory nucleus - Kay, Rachel B.; Brunjes, Peter C. (Frontiers in Cellular Neuroscience, 2014)
Understanding the cellular components of neural circuits is an essential step in discerning regional function. The anterior olfactory nucleus (AON) is reciprocally connected to both the ipsi- and contralateral olfactory bulb (OB) and piriform cortex (PC), and, as a result, can broadly influence the central processing of odor information. While both the AON and PC are simple cortical structures, the regions differ in many ways including their general organization, internal wiring and synaptic connections with other brain areas. The present work used targeted whole-cell patch clamping to investigate the morphological and electrophysiological properties of the AON’s two main neuronal populations: excitatory projection neurons and inhibitory interneurons. Retrograde fluorescent tracers placed into either the OB or PC identified projection neurons. Two classes were observed with different physiological signatures and locations (superficial and deep pyramidal neurons), suggesting the AON contains independent efferent channels. Transgenic mice in which GABA-containing cells expressed green fluorescent protein were used to assess inhibitory neurons. These cells were further identified as containing one or more of seven molecular markers including three calcium-binding proteins (calbindin, calretinin, parvalbumin) or four neuropeptides (somatostatin, vasoactive intestinal peptide, neuropeptide Y, cholecystokinin). The proportion of GABAergic cells containing these markers varied across subregions reinforcing notions that the AON has local functional subunits. At least five classes of inhibitory cells were observed: fast-spiking multipolar, regular-spiking multipolar, superficial neurogliaform, deep neurogliaform, and horizontal neurons. While some of these cell types are similar to those reported in the PC and other cortical regions, the AON also has unique populations. These studies provide the first examination of the cellular components of this simple cortical system.